LAND FORCING CONTROLS PELAGIC-BENTHIC COUPLING IN ADELIE COVE (TERRA NOVA BAY, ROSS SEA) - Povero, P.; Chiantore, M.; Misic, C.; Cattaneo Vietti, R.; BUDILLON, Giorgio (Polar Biology, 2001)
Benthic-pelagic coupling processes were studied in Adelie Cove, a small 70-m deep V-shaped bay, located on the coast of Terra Nova Bay (Ross Sea). This cove is set apart from the open sea by a 12- to 15-m deep sill. Samplings were carried out over 20 days in summer 1997/1998 in the water column, in the sediment and in material collected from the sea-bottom interface by means of a sediment trap. Benthic communities were studied mainly using ROV video tapes. The complex and peculiar interactions between physical, chemical and biological processes, both in the water column and in the sediments, were tightly linked to a katabatic wind pattern, which is the main constraint in water mass circulation. A clear evolution in organic matter distribution and composition was observed. These processes led to a high build-up of materials in the sediments in the deepest part of the cove, which favoured deposit-feeding species and largely contributed to the organic enrichment of the sediments.